Living at the End of Time : Two Years in a Tiny House - Mitchell, John Hanson (Book collections on Project MUSE., 2014)
Now back in print, Living at the End of Time is the story of a Thoreauvian experiment in simple living undertaken in the midst of the fast-paced electronic age.